The effects of aging on host resistance and disease tolerance to SARS‐CoV‐2 infection. (17th November 2020) - Mok, Darren Z. L.; Chan, Candice Yuen Yue; Ooi, Eng Eong; Chan, Kuan Rong
Abstract : The ongoing coronavirus disease 2019 (COVID‐19) crisis caused by severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) has triggered a large‐scale pandemic that is afflicting millions of individuals in over 200 countries. The clinical spectrum caused by SARS‐CoV‐2 infections can range from asymptomatic infection to mild undifferentiated febrile illness to severe respiratory disease with multiple complications. Elderly patients (aged 60 and above) with comorbidities such as cardiovascular diseases and diabetes mellitus appear to be at highest risk of a severe disease outcome. To protect against pulmonary immunopathology caused by SARS‐CoV‐2 infection, the host primarily depends on two distinct defense strategies: resistance and disease tolerance. Resistance is the ability of the host to suppress and eliminate incoming viruses. By contrast, disease tolerance refers to host responses that promote host health regardless of their impact on viral replication. Disruption of either resistance or disease tolerance mechanisms or both could underpin predisposition to elevated risk of severe disease during viral infection. Aging can disrupt host resistance and disease tolerance by compromising immune functions, weakening of the unfolded protein response, progressive mitochondrial dysfunction, and altering metabolic processes. A comprehensive understanding of the molecular mechanisms underlying declining host defense in elderly individuals could thus pave the way to provide new opportunities and approaches for the treatment of severe COVID‐19. Abstract : Elderly patients infected with SARS‐CoV‐2 are at higher risk of developing severe COVID‐19 compared with younger individuals. This outcome could be due to aging‐related alterations in host resistance and disease tolerance mechanisms against pulmonary immunopathology. We review the current knowledge on how aging affects these mechanisms and advocate for more detailed studies on how aging affects viral infection to improve the management of its associated clinical outcome.